Dysregulated Expression of Long Intergenic Non-coding RNAs (LincRNAs) in Urothelial Bladder Carcinoma - Ousati Ashtiani, Zahra (Int J Mol Cell Med, 2017)
Long intergenic non-coding RNA (lincRNA) has been introduced as key regulators of diverse biological processes, including transcription, chromatin organization, cell growth and tumorigenesis. With regard to the potential role of lincRNAs in cancer development, one may postulate that differential expression of lincRNAs could be employed as a tool in cancer diagnosis, prognosis, and targeted therapy. In this study, we aimed to explore the putative correlation between the expression levels of two lincRNAs: LINC00152 and LINC01082 in the bladder cancer (BC), in comparison with its adjacent non-cancerous tissue. Fifty Iranian subjects diagnosed with BC, representing in different stages and grades participated in this study The mRNA expression levels of the abovementioned lincRNAs were comparatively analyzed in cancerous and their adjacent non-cancerous counterpart tissues, of each subject by Real-Time PCR. The expression levels of LINC00152, and LINC01082 were significantly lower in tumor tissues in comparison with their adjacent normal tissues (P<0.001). More notably, in the case of LINC01082 the reduced expression was differentiated by the muscle invasiveness pattern of the tumor (P= 0.05). Our study presents a new finding about the tumor suppressor potentiality of these lincRNAs in BC development that in turn may suggest them as candidate biomarkers. Replicating this study in higher number of BC subjects, coupled with functional analysis, is necessary to investigate interconnections between these RNAs and cancer development, leading to better understanding of cancer biology.